IMPROVEMENT OF THE INTERNAL FORM OF SHOES USING MODERN PROGRESSIVE TECHNOLOGIES - KAPTІUROVA, Daria; CHERTENKO, Lilia; BONDAR, Olexandr; NOS, Olexandra (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In this work we investigate the improvement of comfort of modern shoes due to the improvement of its internal shape, according to the anatomy of the foot. For this purpose, we offer the new method for the development of an ergonomic anthropometrically justified form of the last based on the 3d scanning results of the customer's foot and it`s plaster cast. The reverse engineering method and progressive software was used for that aim. An increased level of shoe comfort is achieved through the use of individual anthropometric insoles, which are designed based on the relief of the plantar surface of the foot obtained by 3D scanning of its plaster cast. An increased level of footwear comfort is achieved, among other things, through the use of individual anthropometric insoles designed on the basis of the relief of the plantar surface of the foot, obtained by 3D scanning of its plaster cast. To create the most comfortable anatomical insoles, the main requirements for their design were analyzed. When designing the shape of the insole, the recommendations of the orthopedist were taken into account.In the development of the last and insoles, progressive software was used: Foot3D for foot 3d scanning, Delcam Crispin LastMaker and PowerShape for shoe last modeling and modifications, and ArtCAM for designing insoles and preparing them for CNC- milling. The manufacturing process of shoe last and anatomical insoles is implemented with the help of only one 3-ways CNC-machine, which ensures a consistent and complex making process without the need for additional equipment. The development of the main elements of the form in the environment of universal progressive programs (PowerShape) provides a further logical converting 3d model to a flat pattern, which contributes to a closed cycle of automation of all design production processes.
Keywords: ergonomic footwear; shoe shape design; anatomical insole; footwear last; CNC-milling